Solitary late metastasis of primary renal cell carcinoid tumor to the extraocular muscles imaged with indium-111 octreotide - Dempsey, Philip; O'Connell, Martin; Bolster, Ferdia (World Journal of Nuclear Medicine, 2021)
A 75-year-old male presented with right eye pain and proptosis. His history was significant for renal cell carcinoma treated with left nephrectomy 2 years previously. Computed tomography (CT) imaging demonstrated a 1.6-cm enhancing lesion in the right retrobulbar space. Surgical biopsy revealed a low-grade metastatic carcinoid tumor. At retrospective review, the primary renal lesion from 2 years prior was rediagnosed as consistent with a renal carcinoid tumor. Indium-111 octreotide single photon emission CT/CT imaging demonstrated a solitary metastasis within the right extraocular muscles. The patient subsequently developed additional metastases within the remaining right kidney and lung.
Keywords: Indium-111 octreotide; ocular metastasis; renal carcinoid tumor